IN PRIMARY EDUCATION INTERDISCIPLINARY TECHNOLOGY OF ORGANIZING INTEGRATED LESSONS (Conferencea, 2024)
In the article, interdisciplinary integration in primary education improvement methodology, the possibilities of developing students' thinking in teaching, the principles of choosing educational materials related to the content of these academic subjects, as well as the fact that interdisciplinary integration of education and upbringing in elementary school students is an important factor in nature protection, and In the course of the lesson, the situation of teaching natural and native language subjects in the context of interdisciplinary integration is presented.